Serum and Urinary Proteomic Signatures Revealing Redox and Metabolic Dysregulation in Acute Achilles Tendon Rupture - Qianman, Bayixiati; Jiasharete, Tuomilisi; Wupuer, Aikeremu; Tuerxun, Aerziguli; Jialihasi, Ayidaer; Mamately, Abuduhilil; Yeerbo, Naertai; Shawutali, Nuerai; Badalihan, Ayinazi; Aisaiding, Amuding; Redati, Darebai; Wuerliebieke, Jianati; et al. (Protein and Peptide Letters, 2025)
IntroductionThe etiology of acute Achilles tendon rupture (ATR) remains unclear. This study conducted a comprehensive case-control study of the proteome profile to gain insights into the potential pathogenesis of acute ATR and identify novel biomarkers.MethodsSerum (iTRAQ) and urine (label-free proteomics) from 15 acute ATR patients and 15 healthy controls were analyzed. Significant differential expression was defined as ≥1.2-fold (serum) or ≥2-fold (urine) change with p < 0.05. Bioinformatics analyses (GO, KEGG, PPI) were performed.Results44 serum and 198 urine proteins were differentially expressed. Enriched pathways included immune response, metabolism, immune response, and redox regulation. protein-protein interaction analysis of the differentially expressed proteins (P < 0.05) highlighted abnormalities in major protein-protein interaction hubs, specifically pyruvate kinase (PKM), peroxiredoxin-1 (PRDX1), phosphoglycerate kinase 1 (PKG1), profilin-1, and apolipoprotein A-IV, observed in the serum and urine samples of acute ATR patients.DiscussionMetabolic dysregulation may affect tendon structure/strength; redox imbalance could promote degeneration. Immune-related proteins may reflect injury responses. Glycolytic enzymes (PKM, PGK1) suggest disrupted energy metabolism.ConclusionProteomic abnormalities in metabolism, immune, and redox pathways, along with key proteins (PKM, PRDX1, PGK1), may contribute to ATR pathogenesis, offering potential biomarkers warranting further validation.
Keywords: biomarkers